An Assessment of Fuel Subsidy Removal and Its Effects on Inflation, Fiscal Capacity, and Household Welfare in Nigeria (2023–2025) - Yusuf Garba Manjo; Ismail Shola Jimoh; Azeez Olanrewaju Saka; Kafaya Abidemi Zubair (Fakultas Pertanian, 2026)
The removal of fuel subsidies in Nigeria in May 2023 marked a major fiscal and economic policy shift under President Bola Ahmed Tinubu's administration, generating widespread debate over its implications for inflation, fiscal sustainability, and household welfare. Although the reform was introduced to reduce government expenditure and improve the allocation of public revenue, concerns emerged about its socio-economic consequences, particularly for vulnerable populations. This research examines the effects of the removal of fuel subsidies on inflation, fiscal capacity, household welfare, and public perception in Nigeria between 2023 and 2025. The research adopts a conceptual and analytical research design, integrating secondary data obtained from the National Bureau of Statistics (NBS), the Federation Account Allocation Committee (FAAC), academic literature, policy reports, and media publications. The findings reveal that removing fuel subsidies significantly increased government fiscal capacity through higher FAAC allocations and expanded public revenue. However, the reform simultaneously intensified inflationary pressures, particularly in transportation, food, and energy sectors, leading to severe increases in the cost of living. The research further found that low-income households, informal workers, women, and rural populations experienced the greatest welfare losses due to declining purchasing power and inadequate social protection measures. Additionally, public dissatisfaction was heightened by the abrupt implementation of policies and ineffective palliative interventions. The research concludes that while removing fuel subsidies may enhance long-term fiscal sustainability, its success depends on effective social protection, transparent governance, and inclusive implementation strategies. The research contributes to existing literature by integrating macroeconomic analysis with household-level experiences, thereby providing a more comprehensive understanding of subsidy reform in developing economies.